Integrasi Nilai Karakter Dalam Pembelajaran Tari Kreasi Melalui Pendekatan Deep Learning Pada Siswa Kelas Vii Di Smpn 2 Ciamis - Dini Indriani; Asti Tri Lestari; Asep Wasta (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to describe the application of the deep learning approach in creative dance learning and its impact on the learning process and character development of seventh-grade students at SMP Negeri 2 Ciamis. The deep learning approach emphasizes meaningful, conscious, and reflective learning through the stages of observing, exploring, practicing, discussing, and reflecting. This study uses a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation during four creative dance learning meetings. Data analysis techniques were carried out through the stages of description, reduction, and selection. The results of the study indicate that the application of deep learning-based creative dance learning can increase students' active involvement, creativity, courage to perform, and understanding of the elements of dance space, time, and energy. In addition, there is a gradual development of student character, especially in aspects of discipline, cooperation, responsibility, creativity, and self-confidence. Learning oriented towards the exploration and reflection process provides a more meaningful learning experience for students. Based on these findings, it can be concluded that the deep learning approach is effective in creative dance learning because it not only improves the quality of the learning process and outcomes, but also contributes to strengthening student character through collaborative and reflective learning experiences.